Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran IPAS Menggunakan Model Discovery Learning di Kelas IV SDN 03 Bandar Buat Kota Padang - Manik, Elizabeth Agnesia; Nelly Astimar (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the improvement of students' learning outcomes in science learning using the Discovery Learning model in class IV SDN 03 Bandar Buat, Padang City. This study is a Classroom Action Research (CAR) using qualitative and quantitative approaches which are carried out in two cycles. Each cycle consists of planning, implementation, observation and reflection. The subjects in this study were teachers and students of class IV SDN 03 Bandar Buat, Padang City, totaling 27 students. The research data were in the form of observations of teaching modules, teacher and student activities, and student learning outcomes using the Discovery Learning model. The data collection techniques used were observation and tests. The results of this study showed an increase in: Learning planning cycle I with a percentage of 84.37% (B) and cycle II 93.75% (SB). Implementation of teacher activities in cycle I with a percentage of 85% (B) and cycle II 93.33% (SB). Implementation of student activities in cycle I with a percentage of 79.99% (C) and cycle II 90% (B). The learning outcomes of students in cycle I obtained an average of 75.33 (C), and cycle II with an average of 83.38 (B). Based on these results, it can be concluded that the Discovery Learning model can improve the learning outcomes of science in class IV SDN 03 Bandar Buat Kota Padang.